2022
DOI: 10.1155/2022/7318950
|View full text |Cite
|
Sign up to set email alerts
|

miR-138-5p Inhibits Vascular Mimicry by Targeting the HIF-1α/VEGFA Pathway in Hepatocellular Carcinoma

Abstract: Tumour vascular mimicry (VM) is the process by which new blood vessels are formed by tumour cells rather than endothelial cells. An increasing number of studies have revealed that the VM process is associated with cancer progression and metastasis. MiR-138-5p has been reported to act as a tumour suppressor in many cancers. However, the role and underlying mechanism of miR-138-5p in hepatocellular carcinoma (HCC) VM remain unclear. In this study, VM density was detected by CD31/periodic acid-Schiff double stain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…HIF-1α is a hypoxia-responsive factor that responds to hypoxia by activating the master regulator of the transcription of many genes and participates in cell energy metabolism, angiogenesis, proliferation, and apoptosis [29]. HIF-1α is upregulated in many tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HIF-1α is a hypoxia-responsive factor that responds to hypoxia by activating the master regulator of the transcription of many genes and participates in cell energy metabolism, angiogenesis, proliferation, and apoptosis [29]. HIF-1α is upregulated in many tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that HIF-1α acts as an oncogene and participates in tumor growth and metastasis [30]. Increasing evidence has demonstrated that VEGFA is an important downstream factor of HIF-1 [29]. Accumulating evidence has shown that VEGFA plays a key role in tumor angiogenesis and vascular mimicry [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, a large body of literature investigated HIF-1 impact on tumorigenesis through other target genes and various biological pathways [ 41 ], including through a crosstalk with NF-kB [ 42 , 48 ], the regulation of pro-oncogenic miRNAs [ 49 , 50 ] known as targets of HIF-1, and key regulators of extracellular matrix degradation by tumor cells, leading to increased invasiveness [ 43 ]. It could thus be of interest to investigate the differential impact of IH vs. SH on these HIF-1 targets.…”
Section: Discussionmentioning
confidence: 99%
“…As research progresses, this vascular mimetic system has been shown to exist in a variety of tumors, including HCC (40), breast cancer (41), and gastric cancer (42), posing a significant threat to patient survival. To date, researchers have identified several proteins that may affect VM in aggressive HCC, including HIF-1a, MMP2, and Twist-1 (43,44), and miRNAs play a crucial part in the VM process by regulating their expression. It has been revealed that miR-138-5p functions as a tumor suppressor in HCC and suppresses VM by binding to the 3′UTR of HIF-1a mRNA and further downregulating the expression of HIF-1a and VEGFA (43).…”
Section: Vascular Mimicrymentioning
confidence: 99%
“…To date, researchers have identified several proteins that may affect VM in aggressive HCC, including HIF-1a, MMP2, and Twist-1 (43,44), and miRNAs play a crucial part in the VM process by regulating their expression. It has been revealed that miR-138-5p functions as a tumor suppressor in HCC and suppresses VM by binding to the 3′UTR of HIF-1a mRNA and further downregulating the expression of HIF-1a and VEGFA (43). Twist-1 is a transcription factor having the structure of a helix-loop-helix.…”
Section: Vascular Mimicrymentioning
confidence: 99%